2018
DOI: 10.2147/tcrm.s178855
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of community-acquired urinary tract infection and appropriateness of treatment in an emergency department in Saudi Arabia

Abstract: IntroductionUrinary tract infection (UTI) is a serious health problem affecting millions of people every year. Inappropriate antibiotic prescriptions put patients at risk and lead to bacterial resistance and elevated costs.AimsStudy aims were to assess the prevalence and antibiotic-treatment patterns of community acquired UTIs, prevalence and types of antibiotic-prescribing errors, and the cost of inappropriate antibiotic use.MethodsThis was a retrospective cross-sectional study conducted over a 3-month period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(104 citation statements)
references
References 32 publications
4
100
0
Order By: Relevance
“…[ 21 ] In their study, also investigating the population under 18-year-old, Alanazi found that E. coli was highly sensitive to nitrofurantoin (92%), followed by ciprofloxacin (81.8%), amoxicillin–clavulanic acid (81.1%), and cefazolin (77.5%). [ 2 ] Moreover, they found a decreasing level of sensitivity of E. coli to co-trimoxazole (55.6%), followed by ampicillin (33.1%). [ 2 ] Rosa et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 21 ] In their study, also investigating the population under 18-year-old, Alanazi found that E. coli was highly sensitive to nitrofurantoin (92%), followed by ciprofloxacin (81.8%), amoxicillin–clavulanic acid (81.1%), and cefazolin (77.5%). [ 2 ] Moreover, they found a decreasing level of sensitivity of E. coli to co-trimoxazole (55.6%), followed by ampicillin (33.1%). [ 2 ] Rosa et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Moreover, they found a decreasing level of sensitivity of E. coli to co-trimoxazole (55.6%), followed by ampicillin (33.1%). [ 2 ] Rosa et al . showed that E. coli isolates were sensitive to trimethoprim-sulfamethoxazol (54%) and to Fluoroquinolones (60%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…False-positive or false-negative results were therefore observed in a limited number of cases. The validation of the FC AST method on clinical urine samples collected from in-patients included two broad-spectrum antibiotic classes, frequently recommended for the emergency treatment of UTIs, i.e., fluoroquinolones (ciprofloxacin) and cephalosporins (ceftriaxone) [ 41 , 42 , 43 ]. The comparative analysis of the FC results with the reference method indicated 100% agreement between the results obtained by the standard assays and those provided by FC AST for ceftriaxone and only a few discrepancies for ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%